Developing paediatric quality indicators for UK general practice - Gill, P (2013)
The overall aim of this thesis is to define a candidate set of quality indicators that are evidence-based, feasible to implement, and have the potential to improve the quality of care provided for children in UK general practice. The indicators were developed using a three-stage process. First, the areas and aspects of care of highest priority for quality indicator development were identified. This was achieved by seeking the views of primary care clinicians and by undertaking a formal analysis of unplanned hospital admissions for ambulatory care sensitive conditions. Then, the evidence-base to underpin indicator development was identified through an overview of Cochrane systematic reviews of interventions relevant to the primary care of children. A search of SIGN and NICE national guidelines was also conducted to inform the evidence-base. Lastly, an expert panel determined the formulation and selection of indicators by applying the RAND appropriateness methodology. This process created a final set of 26 quality indicators in six priority areas: early recognition of potentially serious illness (n=7); child protection and safeguarding (n=4); mental health (n=4); health promotion (n=1); routinely managed conditions (n=6); and general practice management (n=4). The main strength of these indicators is that they reflect a strong professional consensus on their validity and feasibility. The main weakness is that the indicators are underpinned by evidence mainly derived from expert opinion rather than formal research; the requirement for professional consensus means that they do not challenge existing models of care delivery.